2022
DOI: 10.1002/adma.202203330
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Bendable Organic Single Crystal and Transistor Arrays with High Mobility and Durability toward Flexible Electronics

Abstract: materials have intrinsic advantages to meet these requirements, and they can adapt to various complex and extreme flexibility conditions to maintain performance without significant degradation. [7][8][9] However, organic semiconductor films used in flexible electronics are almost polycrystalline or amorphous, which severely limits the availability of high carrier mobility owing to the existence of a large number of grain boundaries, defects, and traps in the film. [9][10][11][12][13] Therefore, organic single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…In previous studies, 2,7-dioctyl [1]­benzothieno­[3,2- b ]­[1]­benzothiophene (C 8 -BTBT) was found exhibiting a high hole mobility in OFET, which is increased about 2–3 orders of magnitude compared with that of BTBT (0.032 cm 2 ·V –1 ·s –1 ). To better understand the role of alkyl substitution in the BTBT derivative, we compared the λ h and λ e values of BTBTT6 with the ones of TBTBT .…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, 2,7-dioctyl [1]­benzothieno­[3,2- b ]­[1]­benzothiophene (C 8 -BTBT) was found exhibiting a high hole mobility in OFET, which is increased about 2–3 orders of magnitude compared with that of BTBT (0.032 cm 2 ·V –1 ·s –1 ). To better understand the role of alkyl substitution in the BTBT derivative, we compared the λ h and λ e values of BTBTT6 with the ones of TBTBT .…”
Section: Resultsmentioning
confidence: 99%
“…However, organic crystals generally have larger band gaps and lower charge carrier populations than inorganic ones. 140 In addition, the rigid structure of organic crystals will lead to certain limitations in the field of flexible electronics. Therefore, it is necessary to develop molecular crystals that possess both high electrical conductivity and high flexibility for practical applications.…”
Section: Electrical Stimuli-responsive Flexible Crystalline Materialsmentioning
confidence: 99%
“…Traditional crystalline materials often suffer from their poor ability of resisting external forces without fragmentation, which greatly hinders their application in flexible devices. Recently, the discovery of flexible organic crystals has remedied this deficiency, and they have attracted numerous attention in the fields of flexible field-effect transistors, 1 wearable devices, 2 flexible displayers, 3 etc. Depending on the type of response to external forces, deformation can be classified into elastic reversible deformation and plastic irreversible deformation.…”
Section: Introductionmentioning
confidence: 99%